RANKING SERVICE QUALITY USING MULTI-CRITERIA DECISION-MAKING METHODS: EXAMPLE OF ERZURUM PROVINCE - Karamaşa, Çağlar (Journal of process management and new technologies, 2021)
In the tourism sector, where competition conditions are getting stiffer, some of the essential factors to hotels stay operational include the need to achieve a sustainable structure and meet the needs and expectations of customers. One of the ways to ensure that the customer expectations and needs are met at the desired level is through service quality factors which are considered to increase customer satisfaction.This study aims to establish the service quality criteria in three-star hotels in Erzurum and to rank the importance levels of the determined criteria. The MAUT method was used to weight the determined criteria. The results of the MAUT method show that the “Quality of Housekeeping” was the most important service quality criteria in three-star hotels. This was followed by "Front Office Service Quality", "Cleanliness", "Reliability", "Restaurant Service Quality" and "Service and Process Flexibility" respectively. The criteria considered as the least important include "Courtesy and Respect Level" and "Price Availability".
Keywords: Tourism; Hotels; Service Quality; MAUT Method